Analisis Pembelajaran Konsep Luas Persegi Panjang di SDN 05 Teramang Jaya Kabupaten Mukomuko Provinsi Bengkulu: Studi Kualitatif melalui Wawancara guru - Dini No Gia; Dina Oktapiani (Yayasan Darussalam Bengkulu, 2025)
This study aims to examine in-depth the teaching methods for the concept of area and length at SDN 05 Teramang Jaya, Mukomuko Regency, Bengkulu Province, including the obstacles faced by teachers, the learning media used, and the difficulties experienced by students in understanding the concept of area. By utilizing qualitative research methods that included indirect observation via video calls, in-depth interviews with teachers, and documentation as a follow-up, this study successfully addressed students' learning in the classroom. The results indicate that teachers use a concrete learning approach utilizing visual media and real objects, which significantly helps students understand the abstract concept of rectangular area. However, various obstacles such as limited measuring tools and variations in students' basic mathematical abilities, particularly in multiplication, pose significant challenges to the learning process. Furthermore, teachers expressed their hope that mathematics learning at the tertiary level will continue to innovate with supporting technology, thus producing more creative, disciplined, and professional prospective teachers. This research is expected to serve as a reference for teachers, prospective teachers, and educational institutions in developing effective and innovative learning methods in the future.